A Legal Challenge to Algorithmic Recommendations: Reconsidering liability shield considerations. - Samuelson, Pamela (Communications of the ACM, 2023)
The article presents information about a lawsuit brought against Google regarding the death of American citizen Nohemi Gonzalez during the terrorist attacks in Paris in 2015. The Gonzalez family blamed YouTube's recommendation algorithms for providing the terrorist organization ISIS with material support. An appellate court found Google had federal immunity due to the Communications Decency Act. The case is now going to the U.S. Supreme Court, which will determine how the Communications Decency Act should be interpreted and Google's liability in the death of Nohemi Gonzalez.